The Avoidance of Activities due to Fear of Falling Contributes to Sedentary Behavior among Community‐Dwelling Older Adults with Chronic Musculoskeletal Pain: A Multisite Observational Study. Issue 11 (16th September 2014) - Stubbs, Brendon; Patchay, Sandhi; Soundy, Andy; Schofield, Pat
Abstract Objective Physical inactivity and sedentary behavior (SB) are leading causes of mortality. We investigated if older adults with chronic musculoskeletal pain (CMP) are more sedentary than a group of similar age and sex without CMP and possible contributory factors to this. Method In this multisite observational study, 285 community‐dwelling older adults (response rate 71%) took part. One hundred forty‐four had CMP (78.4 years, 65.9% female), and 141 formed the comparison group without CMP. Details regarding falls were collected, and all participants completed the brief pain inventory (BPI), modified version of the survey of activities and fear of falling in elderly scale (mSAFFE), and the International Physical Activity Questionnaire (IPAQ) to measure SB. Data were analyzed with hierarchical regression analysis. Results Older adults with CMP spent approximately 3 1/2 hours a day more being sedentary than the comparison group (11.5 hours vs 7.9, P < 0.001). The addition of BPI interference and mSAFFE scores in the regression analysis resulted in an R2 change of 10.4% in IPAQ scores, over and above the variance explained by the background demographic, medical, and mobility factors. Excessive concerns about the consequences of falling did not increase the variance in SB. Within the final model, mSAFFE scores were the largest independent predictor of SB (β = 0.461, P < 0.001). Conclusions Older adults with CMP are significantly more sedentary than those of a similar sex and age without CMP. It appears that the avoidance of activities due to fear of falling is a significant contributory factor to SB in older adults with CMP.